Actividad física y estado nutricional en los estudiantes del Colegio 27 de febrero periodo 2012. - Rivas Peña, Gabriel Raymond (2013)
The present study is of descriptive and traverse type that investigates the association of the practice of physical Activity and the nutritional state in the students from 14 to 17 years, being the sample of 212, with 90 men and 122 women. The survey was used to evaluate the characteristics of physical activity and the intensity was valued in an objective and subjective way with the formula application (frequency heart maxim), and the test of Borg; I weigh and it carves he/she registered directly to establish the Index of corporal mass. The results determined important association among the alteration of the nutritional state for excess and physical activity below the recommendations of OMS, while those of appropriate weight carry out activity more than 1 hour, 3 times per week with moderate intensity and in class of physical education they practice for 30 minutes and in free time for more time and with more intensity in 20%. The nutritional state is of appropriate weight 64,4% of males and obesity 8,9%, in women a weight was determined adapted in 60,7%, bigger percentage in overweight with 32,8% in comparison with the males. Due to the results of this study and to the literary revision a guide was elaborated about the effective promotion of the practice of activity daily physical adolescent and its importance in the health. Key words: physical activity, nutritional state, adolescent.